2015
DOI: 10.3402/jev.v4.29159
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of adipocyte‐derived extracellular vesicles released pre‐ and post‐adipogenesis

Abstract: Extracellular vesicles (EVs) are submicron vesicles released from many cell types, including adipocytes. EVs are implicated in the pathogenesis of obesity-driven cardiovascular disease, although the characteristics of adipocyte-derived EVs are not well described. We sought to define the characteristics of adipocyte-derived EVs before and after adipogenesis, hypothesising that adipogenesis would affect EV structure, molecular composition and function. Using 3T3-L1 cells, EVs were harvested at day 0 and day 15 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
93
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(110 citation statements)
references
References 40 publications
(59 reference statements)
8
93
0
4
Order By: Relevance
“…Connolly et al have reported that EVs from adipocytes are enriched in markers of adipogenesis (such as PREF-1, also known as DLK1, and PPARγ). The amount of PREF-1, a negative regulator of adipogenesis, decreased in EVs derived from cells during the later stages of differentiation (Connolly et al, 2015). Other adipogenesis-related proteins were also detected in adipocyte-derived exosomes including adenylate kinase 2 (AK2), and matrix metalloproteinase-2 and -9 (MMP-2 and MMP-9) (Lee et al, 2015;Aoki et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Connolly et al have reported that EVs from adipocytes are enriched in markers of adipogenesis (such as PREF-1, also known as DLK1, and PPARγ). The amount of PREF-1, a negative regulator of adipogenesis, decreased in EVs derived from cells during the later stages of differentiation (Connolly et al, 2015). Other adipogenesis-related proteins were also detected in adipocyte-derived exosomes including adenylate kinase 2 (AK2), and matrix metalloproteinase-2 and -9 (MMP-2 and MMP-9) (Lee et al, 2015;Aoki et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…For example, BMP4, secreted by adipocytes, can induce ADSCs to undergo adipogenic commitment (Gustafson et al, 2015a). In addition to secreting soluble proteins, adipose tissue also releases extracellular vesicles (EVs) [including exosomes, small membrane vesicles (30-100 nm) that are released by multivesicular bodies fusing with the cell membrane and microvesicles, 100-1000 nm vesicles originated by shedding of the plasma membrane] (Deng et al, 2009;Connolly et al, 2015;Muller et al, 2011;Fleury et al, 2016). However, the size range of exosomes overlaps partially with that of microvesicles, which hinders a complete size-discrimination between these two populations of EVs .…”
Section: Introductionmentioning
confidence: 99%
“…Time-resolved fluorescence was used to assess the surface protein and content of the isolated EVs 223 derived from both normoxia and hypoxia, as described previously [44]. 1x10 9 EVs were loaded onto a 224 high protein binding 96-well plate (Greiner Bio-One, Germany) overnight at 4°C, before non-specific 225 sites were blocked with 1% BSA (R&D Systems) for two hours.…”
Section: ) 215mentioning
confidence: 99%
“…Adipocytes have been shown to produce EVs of heterogeneous sizes which contribute to regulate lipid deposition and angiogenesis, reviewed in . Deng et al .…”
Section: Introductionmentioning
confidence: 99%